Green Mining Efficiency and Improvement Countermeasures for China's Coal Mining Industry - Wang, Ying; Lei, Yuxuan; Wang, Shuyi (Frontiers in Energy Research, 2020)
Abstract：This study defines green mining system as a synergetic operation system composed of mining subsystem and environmental governance subsystem. Based on the concept of green mining, this study identifies the mining subsystem as the first production stage and the environmental governance subsystem as the second production stage through conducting case study in China coal enterprise. To evaluate green mining efficiency, an entire green mining efficiency indicator system is constructed through analyzing the main elements of input and output of the two subsystems in two stage in this article. This study furthermore presents a two-stage combination Data Envelopment Analysis model to assess green mining efficiency composed of mining efficiency and environmental governance efficiency by using the data of 2019 collected from China coal mining enterprise grounded on the constructed indicator system. According to empirical study results, the main findings are unveiled from four aspects. First, the coal enterprise can be divided into three categories in accordance with the efficiency value ranking of two stage and the corresponding synergetic development levels of two stage. Second, the percentage distribution of coal enterprises based on their green mining efficiency level embodies the attributes of spindle structure. Third, the exported parameters information from two-stage combined DEA model can support green mining efficiency improvement as quantitative evidences. Fourth, the policy implications and improvement countermeasures are proposed from three perspectives.